2011
DOI: 10.2215/cjn.08310910
|View full text |Cite
|
Sign up to set email alerts
|

Plasma S100A12 Level Is Associated with Cardiovascular Disease in Hemodialysis Patients

Abstract: SummaryBackground and objectives S100A12 is an endogenous receptor ligand for advanced glycation end products. Cardiovascular disease remains a major cause of morbidity and mortality in patients with chronic kidney disease. In this study, we report cross-sectional data on 550 hemodialysis patients and assess the relationship between plasma S100A12 level and cardiovascular disease.Design, setting, participants, & measurements A cross-sectional study of 550 maintenance hemodialysis patients was conducted. We inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 31 publications
5
51
0
Order By: Relevance
“…However, we did not find a reduction in EN-RAGE levels after calcitriol treatment; in fact, we observed an increase. The sRAGE levels we detected were similar to those in previous reports (Kalousova et al 2006;Nakashima et al 2010), although our EN-RAGE levels were relatively higher than those previously reported (Mori et al 2009;Nakashima et al 2010;Shiotsu et al 2011;Zakiyanov et al 2011). The precise reason for such discrepancy is not clear.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, we did not find a reduction in EN-RAGE levels after calcitriol treatment; in fact, we observed an increase. The sRAGE levels we detected were similar to those in previous reports (Kalousova et al 2006;Nakashima et al 2010), although our EN-RAGE levels were relatively higher than those previously reported (Mori et al 2009;Nakashima et al 2010;Shiotsu et al 2011;Zakiyanov et al 2011). The precise reason for such discrepancy is not clear.…”
Section: Discussionsupporting
confidence: 89%
“…We also hypothesized that SHP status would affect EN-RAGE levels, as the positive relationship between 1,25D and sRAGE and the inverse relationship between sRAGE and EN-RAGE were discovered after calcitriol treatment, although this warrants further investigation. Because the observed increase in sRAGE and reduction in EN-RAGE may be related to CVD, hypertension, and atherosclerosis in patients with ESRD (Mori et al 2009;Nakashima et al 2010;Shiotsu et al 2011;Wu et al 2011;Kim et al 2012), the previously unreported relationship between SHP and EN-RAGE levels merits additional study.…”
Section: Discussionmentioning
confidence: 99%
“…27 However, RAGE ligands do accumulate in the context of uremia and are correlated with cardiovascular mortality. 31,40,41 Moreover, Bro et al 27 reported that the administration of anti-RAGE antibodies limited uremia-induced atherosclerois in mice. RAGE promotes the migration of various cell types.…”
Section: Figure 5 Serum Amyloid a (Saa) Induces The Receptor For Advmentioning
confidence: 99%
“…36 Levels of S100A12 mRNA in peripheral leukocytes, and protein in serum from chronic kidney disease patients with CVD are elevated 37 and higher in hemodialysis patients with atherosclerosis than in controls, 38 possibly reflecting a systemic inflammatory state. A cross-sectional study 39 suggests S100A12 involvement in the progression of atherosclerosis as a complication of endstage renal disease. S100A12 levels correlate positively with maximum carotid intima-media thickness, 38 prevalence of peripheral arterial disease, carotid atherosclerosis and/or plaque formation, 40 and predict CVD-related mortality.…”
Section: Calgranulins In Diseases Predisposing To Cardiovascular Riskmentioning
confidence: 99%